USING MULTI SENSORY APPROACH FOR TEACHING ENGLISH SKILLS AND ITS EFFECT ON STUDENTS’ ACHIEVEMENT AT JORDANIAN SCHOOLS - Jubran, Sereen (European Scientific Journal, ESJ, 2012)
The purpose of this study is to investigate the effect of using Multi Sensory Approach for teaching English language skills on the tenth grade students’ achievement in English at Jordanian public schools. To achieve the purpose of the study, a pre/post-test was constructed to measure students’ achievement in English. The test consisted of thirty items. The sample of this study consisted of 122 students; fifty seven male students and sixty five female students from tenth grade students at Aisheh Bent el Rasoul secondary school for girls and Firas Al Ajlouni secondary school for boys in Amman the fifth Directorate of education during the second semester of the academic year 2010/2011. The subjects of the study were distributed into two groups (experimental group and control group). The experimental group was taught English language using multi sensory approach while the control group was taught English language using the traditional way of teaching. The subjects were 31 male students for the experimental group and 26 male students for the control group, while the female students for the experimental and control group were 32 and 33 respectively. Those subjects were distributed into two purposefully selected sections at Aisheh Bent el Rasoul secondary school for girls and Firas Al Ajlouni secondary school for boys in Amman. Descriptive statistical analyses were used (means and standard deviation) for the pre and post- tests of students’ English language test to experimental and control groups. Comparison statistical methods were used (Two Way ANOVA) analysis of variance to make a comparison between the control and the experimental groups and gender variable (male and female). The findings of the study indicated that there were statistically significant differences in the post- test between the control and the experimental groups in favor of the experimental group who were taught using multi sensory approach, and there was no statistically significant difference in the students’ achievement due to gender. There was no statistically significant difference due to the interaction between gender and group. The researcher proposed some recommendations to enhance the effect of using multi sensory approach in teaching English language skills on students’ performance such as conducting further studies in other schools and other areas in the kingdom.